Pengaruh Pendidikan, Latihan Dan Kepemimpinan Terhadap Kinerja Pegawai Dengan Motivasi Sebagai Variabel Intervenig - Lestari, Tutik; Ahmadi, Slamet; Cecep, Cecep (Fakultas Ekonomi Universitas Gresik, 2023)
Education & Training Research (Training), Leadership and Motivation are factors that are thought to be relatively large in influencing the Performance of Military Staff General Staff of the Jayakarta/Jayakarta Regional Military Command in East Jakarta. To prove this effect, this research was conducted with the aim of analyzing the effect of Education & Training (Training), Leadership with Motivation as an Intervening Variable on Military Personnel of the General Staff in East Jakarta. The object of this study was taken from the General Staff Military Personnel population in East Jakarta. With a total sample of 107 out of 146 populations calculated using the Slovin formula at a 5% error margin, data collection used a closed questionnaire and there were 5 rating scales. Data analysis was carried out using the Statistical Package for Social Science (SPSS), double linear registration was used as an analytical tool while hypothesis testing was carried out by t-test and F-test and path analysis was used to test the effect of intervening variables. The results of this study indicate that Education & Training (Training) has a positive and significant effect on motivation. Leadership has a positive and significant effect on motivation. Training has a positive and significant effect on performance. Leadership has a positive and significant effect on performance. Motivation has a positive and significant effect on performance. Training has no effect on employee performance through motivation. And leadership has no effect on employee performance through motivation.